Three-Dimensional Analysis of PT Pertamina's Customer Oriented Perspective of New Public Management - Gonzales, Ririn; Putri, Rizki Amalia; Sari, Siska Puspita (Universitas Airlangga, 2023)
In the past few years, the country's manufacturing companies have been caught in a vicious cycle caused by poor working capital to affect the investment surplus. Using the New Public Management approach is considered suitable for carrying out the process of public value creation. There is limited literature which discusses the importance of customers' role from the perspective of New Public Management. This research discusses about customer-oriented public services precisely at PT Pertamina. This research aims to see the importance of customer position in a company because their relationship is important as customers need products and companies need trust from customers so that profitability is maintained. This research method is descriptive analysis. The results of study show that Pertamina in the NPM approach seen from the aspect of orientation towards customers has met customer needs. From the affective dimension, Pertamina always provides motivation to employees with various awards, providing good attitude and responsiveness, both to customer and fuel supply distribution. The cognitive dimension shows that Pertamina is always reactive in providing information through various types of services, preparing strategies to respond to competitors, and responsiveness in inconsistencies conditions. From responsiveness dimension shows that Pertamina can provide services align with customer needs such as providing services that can be reached by customers. Pertamina is able to prioritize customers by always paying attention to the service commitment provided making it one of the State-Owned Enterprises that could increase the capacity of services quality to the community as it should. Keywords: New Public Management, Reinventing Government, Customer Oriented